Peran Minat Investasi di Kalangan Generasi Z Kota Bandung: Kajian Pengetahuan dan Motivasi Terhadap Keputusan Investasi - Aura Gista Irgina Putri; Agus Maolana Hidayat (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Capital market investment is growing very rapidly with the dominance of investors aged ≤ 30 years or Generation Z. However, along with the increasing number of investors, the number of fraud cases also increases. In this context, knowledge and motivation are two important factors that influence investment decisions. In addition, investment interest also functions as a bridge connecting knowledge and motivation with investment decision making. The purpose of this study is to determine the role of investment interest among Generation Z in Bandung City by considering the influence of knowledge and motivation on investment decisions. Quantitative methods are used in this study, where surveys are applied to collect and process data. The population studied was Generation Z investors in Bandung City, with a sample of 394 respondents selected through purposive sampling techniques. To test the hypothesis, the researcher used the Structural Equation Modeling - Partial Least Square (SEM-PLS) technique. The findings in this study indicate that investment interest can mediate the relationship between knowledge and motivation on investment decisions of Generation Z in Bandung City